The Antithesis of the Accusatory System. A proposal on the regulation of the Informal and Justified preventive prison towards a digital justice and according to the Human rights - Solís Buitrón, Victor Manuel (2020)
Last August of this year, the Universidad Nacional Autónoma de México, through the Law School, by initiative of the College of Professors of Criminal Law, in response to the suspension of academic activities, as a result of the pandemic that afflicts the world arising from the SARS-Cov2 virus, taking advantage of digital platforms available to people at this time as a tool to use to communicate at a distance, organized the First International Virtual Congress of Criminal Law. In this event, more than 130 academics from different Latin American Universities participated as speakers, who presented on topics of the criminal legal reality, both substantive and adjective, in the panels that were organized by themes that addressed different concepts in these specialties. The Congress was embellished by Magisterial Conferences issued by Masters Emeritus and Deans of the Faculty of Law of the UNAM and other law schools of invited countries.The importance of the Congress surprised the Academic Forum, almost twenty thousand people registered and approximately two million of them accessed the event that was transmitted and broadcast on social networks through the Facebook platform “Live streaming”. From the approaches that were most emphasized in the presentations, the concern of the present article is born. Specifically, it highlights concerns about exercise, it highlights the concern about the arbitrary exercise of criminal law due to its punitive nature and the importance of limiting the excess in its application, respecting in general the human rights of individuals and, in particular, those recognized for the parties in the procedural rules, this in equity with the Fundamental Principles of the Prosecution Systems in the accusatory model, already adopted in practically all democratic countries in Latin America. This highlights the need for a new definition of preventive prison, conceived now as a precautionary measure and its intimate relation with the principle of the “Presumption of Innocence”, in whose application there must be absolute communion, a necessary condition in order to have a profound and definitive vision in the protection of Human rights. Puede conocer los comentarios del autor/a sobre el artículo aquí: https://youtu.be/wIBwCxq31kk